Overview of C3 Glomerulopathy - Master Sankar Raj, Vimal; Gordillo, Roberto; Chand, Deepa H. (Frontiers in Pediatrics, 2016)
Abstract: C3 glomerulopathy is an umbrella term which includes several rare forms of glomerulonephritis (GN) with underlying defects in the alternate complement cascade. A common histological feature noted in all these GN is dominant C3 deposition in the glomerulus. In this review, we will provide an overview of the complement system as well as mediators, with an introduction to pharmaceutical agents that can alter the pathway.